Simplified selection criteria for patients with longer or unknown time to treatment predict good outcome after mechanical thrombectomy - Nagel, Simon; Herweh, Christian; Pfaff, Johannes; Schieber, Simon; Schönenberger, Silvia; Möhlenbruch, Markus Alfred; Bendszus, Martin; Ringleb, Peter A. (Journal of neuroInterventional surgery, 2019)
Objective: To identify simplified selection criteria for mechanical thrombectomy (MT) in longer and unknown time windows. - Methods: Patients with large vessel occlusion (LVO) in the anterior circulation who underwent MT between January 2014 and November 2017 were identified from the local registry. Patients were selected for analysis if they met the current guideline recommendation for MT treatment except for time window (HERMES-like) and were divided according to time they were last seen well (LSW): LSW <6 hours or LSW >6 hours before MT. The primary endpoint, good outcome, was modified Rankin scale score 0-2 on day 90. Safety outcomes were mortality on day 90 and symptomatic intracranial hemorrhage (sICH). Univariate and multivariate analysis were performed for good outcome in HERMES-like patients. - Results: In total, 752 patients were identified and 390 patients (51.9%) fulfilled the HERMES-like criteria. Despite differences in baseline parameters, more diffusion-weighted imaging (DWI) (43.9% vs 11.3%, p<0.001) and fewer cases of thrombolysis (32.7% vs 77%, p<0.001), patients LSW >6 hours (n=107) did not differ in the primary and secondary endpoints: good outcome (44.9% vs 44.9%, p=1.0), mortality (14% vs 15.2%, p=0.87), and sICH (5.6% vs 6%, p=1.0). After multivariate regression analysis, independent predictors of good outcome remained: age, OR=0.96 (95% CI 0.95 to 0.98); National Institutes of Health Stroke Scale score, OR=0.92 (95% CI 0.89 to 0.96); Alberta Stroke Programme Early CT Score (ASPECTS), OR=1.26 (95% CI 1.06 to 1.49); general anesthesia, OR=0.2 (95% CI 0.04 to 0.99), and successful recanalization, OR=12 (95% CI 4.7 to 30.5); but not treatment time and DWI or CT perfusion at baseline. - Conclusion: Patients with proven LVO in unknown and longer time windows may be selected for MT based on ASPECTS and clinical criteria.